2017
DOI: 10.17509/jaset.v9i1.5446
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Good Government Governance Dan Ukuran Legislatif Terhadap Kinerja Pemerintah Daerah (Studi Pada Pemerintah Provinsi Di Indonesia)

Abstract: Abstract. The variables tested in the study consist of Good Government Governance measured by the rank of Indonesia Governance Index (IGI) and the size of the legislative by using the number of members of theAbstrak.Variabel yang diuji dalam penelitian ini penelitian ini terdiri dari Good Government Governance diukur dengan hasil peringkat Indonesia Governance Index (IGI)dan ukuran legislatif dengan menggunakan jumlah anggota DPRD provinsi, serta kinerja pemerintah daerah diukur dengan tiga proksi yaitu PDRB P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A good government will improve performance and services for the community, and will reduce corruption (IFAC, 2013). Hutapea and Widyaningsih (2017) confirmed that poor government management brings negative impacts to the government, the community, and other parties-one example is the lack of public trust in the government, which worsens crucial issues in the community.…”
Section: Public Interest Statementmentioning
confidence: 95%
See 2 more Smart Citations
“…A good government will improve performance and services for the community, and will reduce corruption (IFAC, 2013). Hutapea and Widyaningsih (2017) confirmed that poor government management brings negative impacts to the government, the community, and other parties-one example is the lack of public trust in the government, which worsens crucial issues in the community.…”
Section: Public Interest Statementmentioning
confidence: 95%
“…The results of this study can be used by subsequent researchers to assess the effectiveness of the implementation of the new role of internal auditors in various environments of government organizations. (Hutapea & Widyaningsih, 2017). Alternatively, outcome-oriented approaches can also be used, such as value for money or efficiency, effectiveness, economic performance, and financial performance (Basri & Nabiha, 2014;Sutopo et al, 2017).…”
Section: Public Interest Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurdin et al, 2019), (Azzindani, 2020), (Kewo & Mamuaya, 2019), (Susbiyani, 2015). (Lestiawan & Jatmiko, 2016), (Nurwanda & Garis, 2019), (Hutapea & Widyaningsih, 2017), (Wiguna et al, 2017), (Widiari et al, 2016), , (Yudhasena & Putri, 2019), (Supratiwi et al, 2019). (Meyanti, 2019), (Firmansyah & Rahmawati, 2020), (Rahayu et al, 2021), (Icih, 2018), (Sofia & Purnomo, 2015), (Septariani, 2017) Ungu (Firmansyah, 2017), (Hidayati & Widiastuti, 2019), (Tullah et al, 2018), (Yudhasena & Putri, 2019)…”
Section: Quality Of Financialmentioning
confidence: 99%
“…Pemenuhan janji dan perumusan kebijakan yang memihak rakyat merupakan sesuatu yang penting karena ini merupakan perwujudan akuntabilitas suatu pemda, dimana makna dari akuntabilitas adalah pertanggungjawaban. Hasil penelitian ini sesuai dengan penelitian yang dilakukan oleh Hutapea & Widyaningsih (2017) [21] dan Vegy & Serly (2019) [22] bahwa tata kelola pemerintah tidak berpengaruh terhadap kinerja pemerintah daerah.…”
Section: Pembahasanunclassified